Options for Management of Fusarium Wilt of Strawberry in California. (30th November 2016) - Gordon, Thomas R.; Daugovish, Oleg; Koike, Steven T.; Islas, Christina M.; Kirkpatrick, Sharon C.; Yoshisato, Jenna A.; Shaw, Douglas V.
ABSTRACT: The emergence of Fusarium wilt, caused by Fusarium oxysporum f. sp. fragariae, as a problem for strawberry production in California has been associated with delivery of fumigants to beds through drip-lines rather than flat-fumigation of an entire field. Our research shows that bed fumigation fails to eliminate propagules of the Fusarium wilt pathogen, which remain particularly abundant in bed shoulders at a depth of 30 cm. Controlled environment studies confirmed that inoculum at this depth could cause disease. Screening of currently grown strawberry cultivars documented a wide range of susceptibilities to Fusarium wilt, with some being highly resistant.